Effect of Cashflow on the Networth of construction firms in Nigeria - Akparhuere, Godwin Oghenekohwo; EMEJULU, Callistus Emeka; Nwoha, Chike Earnest (Archives of Business Research, 2021)
The main objective of this study is to ascertain the effect of Cashflow on the Networth of construction firms in Nigeria. The specific objectives are to: determine the relevance of operating activities to Networth of construction firms in Nigeria; ascertain the relevance of investing activities to Networth of construction firms in Nigeria; and to verify the relevance of financing activities to Networth of construction firms in Nigeria. The study adopted the ex-post facto research design and the data for analysis were obtained from the annual reports and financial statements of accounts of two (2) sampled firms from the construction industry in Nigeria, namely Julius Berger Nig. Plc and MISTA Nig. Ltd. The data collected covered 10 years (2009-2018) for Julius Berger and MIXTA Nig. Ltd and were then pooled and analysed using SPSS v 20.0, the tools of analysis being correlation coefficient (r), coefficient of determination (R2), F-ratio (ANOVA), t-test (for the tests of hypotheses), and the regression analysis for fitting the models. Findings revealed that operating activities cost, investing activities costs and financing activities cost have no significant relevance to Networth of construction firms in Nigeria. The conclusion was that the construction industry in Nigeria, though bereft of adequate amount of data to accomplish the aim of this study, has at least opened a new dimension about this contemporary issue in research. That would be a welcome dimension in our effort to improve the Building and Construction sector for development. Based on the findings, the study recommends that Managers should adopt cost reduction practices that would increase efficiency of operations that could translate to higher Networth; more investment activities should be encouraged by Construction firms so as to consolidate on the present situation; and the managements of Construction firms are advised to increase the financing activities in the industry so as to improve total assets. This will grow more assets and reduce the size of liability of the firms in the future. The implication is that since all the three components do not have significant effect on the Networth of construction companies in Nigeria, it might be difficult to generalize the findings. Therefore, it might need further investigation using larger sample size and different analytical approaches to ascertain the effect of Cashflow on Networth of Building and Construction firms in Nigeria.